Galectin-10 Is Released in the Nasal Lavage Fluid of Patients with Aspirin-Sensitive Respiratory Disease - Ma. Cristina Negrete-Garcia; Carla Yoneli Jiménez-Torres; Noe Alvarado-Vásquez; A. Rosalía Montes-Vizuet; J. R. Velázquez-Rodriguez; M. Carmen Jimenez-Martinez; Luis Manuel Teran-Juárez (The Scientific World Journal)
The aim of this work was to determine the presence of galectin-10 in nasal lavage fluid (NLF) of patients with aspirin-sensitive respiratory disease (ASRD) before and after challenge with L-ASA (aspirin) by ELISA. Fifteen ASRD patients, ten aspirin-tolerant asthmatics (ATA), and fifteen healthy controls (HC) were studied. The baseline presence of Galectin-10 in PBMC was determined using real time PCR. Galectin-10 was evaluated in tissue of nasal polyps by western blot. Our results showed a lower expression in PBMC of ASRD patients than in ATA and healthy controls. However, a higher concentration of galectin-10 in NLF was found in ASRD patients before and after L-ASA challenge; western blot confirmed a high expression of galectin-10 in tissue from nasal polyps obtained from ASRD patients. Our results suggest a probable role of galectin-10 in the inflammatory response observed in ASRD patients; however, confirmatory studies are needed.